2010
DOI: 10.1007/s11240-010-9695-7
|View full text |Cite
|
Sign up to set email alerts
|

A simple cryopreservation protocol of Dioscorea bulbifera L. embryogenic calli by encapsulation-vitrification

Abstract: Embryogenic calli of Dioscorea bulbifera L. were successfully cryopreserved using an encapsulationvitrification method. Embryogenic calli were cooled at 6°C for 5 days on solid MS medium (Murashige and Skoog 1962) containing 2 mg L -1 Kinetin (Kn), 0.5 mg L -1 a-naphthalene acetic acid (NAA) and 0.5 mg L -1 2,4-dichlorophenoxy-acetic acid (2,4-D). These were prior precultured on liquid basal MS medium enriched with 0.75 M sucrose at 25 ± 1°C for 7 days. Embryogenic calli were osmoprotected with a mixture of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Recovery in the control explants was not significantly affected till 3 days-treatment (Table 1). Our findings showed that the application of a correct exposure time and concentration of sucrose is critical to insure re-growth in Morus alba as previously shown in cryopreservation of shoot apices of temperate and tropical species and embryogenic tissue of Dioscorea bulbifera and Pinus nigra (Engelmann et al 2008 and references within reported;Ming-Hua and Sen-Rong 2010;Salaj et al 2011).…”
Section: Encapsulation-dehydrationsupporting
confidence: 80%
“…Recovery in the control explants was not significantly affected till 3 days-treatment (Table 1). Our findings showed that the application of a correct exposure time and concentration of sucrose is critical to insure re-growth in Morus alba as previously shown in cryopreservation of shoot apices of temperate and tropical species and embryogenic tissue of Dioscorea bulbifera and Pinus nigra (Engelmann et al 2008 and references within reported;Ming-Hua and Sen-Rong 2010;Salaj et al 2011).…”
Section: Encapsulation-dehydrationsupporting
confidence: 80%
“…Tissues conserved in vitro at low temperature might show some physiological disorders during conservation followed by a dramatic decrease in survival and regrowth ability (Tahtamouni and Shibli 1999). Moreover, maximum successes of Dioscorea bulbifera L. calli were observed by using of 0.75 M sucrose at 4°C for 7 days (Ming-Hua and Sen-Rong 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Tissue culture provides an alternate method for large-scale propagation of threatened and endangered plants, including orchid micropropagation using various explants. Somatic embryogenesis is one of the most promising approaches for plant propagation due to the production of large numbers of plantlets [10], the possibility of producing synthetic seeds [11], [12], the ability to store and rapidly mobilize germplasm for cryopreservation [13], the opportunity for genetic manipulation [14] and production of bioactive compounds within a short period of time [15], [16]. It is necessary to develop a method for mass clonal propagation and conservation to satisfy the pharmaceutical demand of this high value medicinal plant.…”
Section: Introductionmentioning
confidence: 99%